Meningitis and intracranial abscess due to Mycoplasma pneumoniae in a B cell-depleted patient with multiple sclerosis - Madžar, Dominik; Nickel, Florian; Rothhammer, Veit; Gölitz, Philipp; Geißdörfer, Walter; Dumke, Roger; Lang, Roland (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Mycoplasma pneumoniae, a frequent respiratory pathogen, can cause neurological disease manifestations. We here present a case of M. pneumoniae as cause of meningitis and occurrence of an intracranial abscess as a complication of mastoiditis with septic cerebral venous sinus thrombosis in a patient with multiple sclerosis on anti-CD20 therapy.
CRIS-Team Scopus Importer:2024-09-20
Keywords: Abscess; Anti-CD20 antibody; Complication; Mastoiditis; Multiple sclerosis; Mycoplasma pneumoniae; Ocrelizumab; Rituximab; Septic cerebral venous sinus thrombosis